Barriers to ICT use in science teaching: a comparative analysis of Malaysian and Saudi science teachers - Tunku Ahmad, Tunku Badariah; Al-Turki, Eman Mohammed; Nur, Abdul Hamid Busthami; Nordin, Mohamad Sahari (2013)
Despite the efforts expended by the governments of Malaysia and Saudi Arabia to promote science teachers’ use of ICT in the classroom, the ICT uptake among these teachers remains slow and dismal. This article reports on a study undertaken to explore and understand the barriers that prevented science teachers in both countries from using ICT in their science instruction. A total of 282 science teachers from selected schools (53.5% Malaysian and 46.5% Saudi) responded to the survey. Principal components analysis (PCA) run on the data extracted four underlying factors that prevented the respondents from using ICT to teach, namely attitude towards ICT use, access to ICT at school, beliefs about ICT use and technical support provided by the school to promote ICT utilization. Among these four factors, attitude towards ICT emerged as the largest inhibitor, explaining about 25.5% of teachers’ lack of ICT uptake in the science classroom. T-test results revealed significant differences between Malaysian and Saudi teachers in terms of access to ICT and technical support, but no significant difference in terms of attitude and beliefs about ICT use. The results corroborated previous findings that teacher factors tend to outweigh school factors in promoting or hindering teachers’ uptake of technology